HOW MUCH HEAVIER IS A “HOE” FOR WOMEN? WAGE GENDER DISCRIMINATION IN THE BRAZILIAN AGRICULTURAL SECTOR - Schwaab, Kalu Soraia; Dutra, Vanessa Rabelo; Marschner, Paulo Fernando; Ceretta, Paulo Sergio (Contextus - Revista Contemporânea de Economia e Gestão, 2019)
This paper aims at analyzing the existence of wage differentials by genders in the agricultural labor market in the Brazilian rural area, with the purpose of verifying if the differentials are due to differences in explained characteristics or discriminatory. Equations were estimated and the wage differential detailed decomposition with microdata from the PNAD 2015 with the Heckman's correction. The method used was the decomposition of Oaxaca-Blinder. The main results show that the wage/hour of men is 157.62% higher than that of women, and the effect of discrimination is 108.38% this gap. The main conclusion indicates that the gender wage differential decreases with the formality of work and with the increase of hours worked by women. It is worth nothing that the results provide the visualization of gender discrimination in the rural labor market, adding contributions to the empirical studies on wage differentials.